DHP23002 as a next generation oral paclitaxel formulation for pancreatic cancer therapy - Jang, Eunseo (PLoS One, 2019)
OBJECTIVE: This study aimed to develop a new oral paclitaxel formulation (DHP23002) and to evaluate its absorption and antitumor effects in a pancreatic tumor mouse model. METHODS: To investigate the oral absorption of DHP23002, a newly developed lipid-based orally active paclitaxel formulation, a pharmacokinetic study of DHP23002, was conducted in mice (62.5 and 125 mg/kg). Moreover, to evaluate the antitumor effect of DHP23002 in pancreatic cancer treatment, the drug was administered to female athymic nude mice at 0 (vehicle), 25, 62.5, and 125 mg/kg on alternate days; the efficacy of the agent was compared with the efficacy of intravenous Taxol(®) injections at 10 mg/kg once per week. After 3 weeks of administration, tumor growth in mice belonging to each group was further monitored for 4 weeks after discontinuing medication. Moreover, to examine paclitaxel (DHP23002) accumulation in the tumor tissue, the amount of paclitaxel in tumor/blood was quantified using liquid chromatography with quadruple-TOF mass spectrometry. RESULTS: In the mouse pharmacokinetic study, oral Taxol(®) showed a negligible absorption, whereas DHP23002 showed a high absorption rate dependent on dosage, with a bioavailability of approximately 40% at a dose of 62.5 mg/kg. In efficacy-related studies, DHP23002 administration at a dose of 25, 62.5, or 125 mg/kg on alternate days for 3 weeks showed a superior tumor inhibitory effect of 80%, 92%, and 97% in a xenograft mouse model, respectively, after 7 weeks. Paclitaxel accumulation in tumors persisted for >24 h in mice, when orally administered once at doses of 25, 62.5, and 125 mg/kg DHP23002. CONCLUSION: Oral chemotherapy with DHP23002 showed excellent absorption in animals owing to a strong antitumor activity in a pancreatic cancer mouse model. This demonstrates that paclitaxel is largely distributed and persists for a prolonged period at the tumor site owing to oral DHP23002 administration.